Prospective study to assess functional outcomes in patients undergoing single bundle arthroscopic reconstruction of primary anterior cruciate ligament tear comparing with bone quadriceps tendon versus hamstring tendon autograft - Khanna, Gagan; Attri, Raman; Sharma, Rohit (International Journal of Research in Orthopaedics, 2020)
Background: Anterior cruciate ligament (ACL) injuries are one of the most common ligament injuries of knee. Arthroscopic ACL reconstruction has become the standard of care for ACL injuries in the active patient. In present study good bone quadriceps tendon (BQT) autograft and hamstring tendon (HT) autograft will be used for primary arthroscopic ACL reconstruction and its data regarding clinical and functional results will be evaluated and compared. Methods: Sixty patients underwent isolated ACL reconstruction. 30 underwent ACL reconstruction with the BQT and 30 with the HT. The same surgical technique, fixation method and postoperative protocol were used in both groups. Functional outcome in terms of International Knee Documentation Committee (IKDC) score, joint stability (anterior drawer, Lachman, pivot shift), anterior knee pain and isokinetic strength was evaluated. Results: IKDC score in bone quadriceps tendon and hamstring tendon group after 9 months follow up showing no statistical significance. The negative Lachman component was higher in the BQT group than in the HT group. There was no difference between groups in terms of isokinetic strength. Conclusions: Our study shows no statistically significant difference between both groups.